Autonomy in National Olympic Committees 2017 - An autonomy index - Wickstrøm, M. A.; Alvad, S. (Play the Games, 2018)
The aim of this index is to provide an overview of relationships between the National Olympic Committees (NOCs) and national governments in terms of direct and formal overlap between NOC leadership and positions in the national government by late 2016.